Study of the infrared, mid-infrared, visible and ultraviolet spectra of copper chloride CuCl2. 2H2O Copper chloride (Journal of the College of Basic Education, 2022)
The spectroscopic study of the copper chloride molecule (CuCl2.2H2O) was carried out in the wide spectrum range 〖cm〗^(-1) (40000 - 410), including the medium infrared, and the absorption bands of the basic transitions within this region were identified to the symmetric bond stretch ( ∑^+) 1Ʋ, asymmetric stretching of bonds (∑^+) 3Ʋ, which are non-degenerate vibrations, and symmetric angle bending Ʋ2(π) doubly degenerate. All these bands are active in the infrared and Raman field, due to the weak symmetry of this molecule.